El mito y las uniones imposibles. Análisis de la trama de un relato de los indígenas pilagá (Chaco Central) - Idoyaga Molina, Anatilde (Revista Española de Antropología Americana, 2008)
The author, based on original material, focuses on the impossible amorous unions between human beings and mythical characters, among the Pilaga Indians from the Argentine Chaco. To accomplish this, she analyses the myth centred in the union between a Star and just a man. Exploring the plot, the author underlines the myth’s message, and claims that it means to expose the impossible unions, the ones which go against the social and cosmic order of the society.